Current and future prospects for hemophilia gene therapy. Issue 7 (2nd July 2016) - Ward, Peter; Walsh, Christopher E.
ABSTRACT: Here we review the recent literature on Hemophilia gene transfer/therapy. Gene therapy is one of several new technologies being developed as a treatment for bleeding disorders. We will discuss current and pending clinical efforts and attempt to relate how the field is trending. In doing so, we will focus on the use of recombinant Adeno-associated viral (rAAV) vector-mediated gene transfer since all currently active trials are using this vector. Recent exciting results embody nearly 20 years of preclinical and translational research. After several early clinical attempts, therapeutic factor levels that can now be achieved reflect several modifications of the original vectors. Patterns of results are slowly starting to emerge as different AAV vectors are being tested. As with any new technology, there are drawbacks, and the potential for immune/inflammatory and oncogenic risks have emerged and will be discussed.